If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + y = 30 Solving 23 + y = 30 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + y = 30 + -23 Combine like terms: 23 + -23 = 0 0 + y = 30 + -23 y = 30 + -23 Combine like terms: 30 + -23 = 7 y = 7 Simplifying y = 7
| -1(2)(-2)= | | 6(3)+3(-2)= | | -6u^2+11u+20= | | 3-(-2)(5)= | | 6u^2-11u-20= | | 3+-2(5)= | | 10r^2-13r=-4 | | -26=-12u-9+7u | | 3-3(-1)= | | 11x-6=65 | | 7(-2)-3= | | 3a^2+5a+2=0 | | 9+2(-1)= | | 36-4x=16+6x | | -1(-1)= | | -x^2+2=x-4 | | -5(-2)+8(-3)= | | y^3-7y^2+8y+16=0 | | 8-(-8)+(-3)= | | -5(5)+4(4)= | | X*24=73.5 | | (3+x)(5x+7)=0 | | 7.63x^2+2.79x=5.32 | | -14-(-4)= | | -18+13= | | 6-2x=-10x+20 | | -12+(-13)= | | -11(-5)= | | -8+5-7= | | 4(-6)= | | 176=2x-4(5x-8) | | -45*(-5)= |